Narratives on the present and the future in the time of COVID-19 pandemic: Uncertainty, subjective feeling and the role of positive anticipatory states - Biassoni, Federica; Balzarotti, Stefania; Abati, Daniela; Salducco, Alice; Gnerre, Martina (Frontiers in Communication, 2023)
Background: The aim of the present study was to investigate the relationship between certainty, positive anticipatory states, and positive feelings by analyzing written narratives collected during the COVID-19 pandemic lockdown in April 2020. Methods: A total of 1090 Italian participants were asked to write two narratives (one about the present and one about their representation of the future). The corpus was analyzed with the Linguistic Inquiry and Word Count software package (Pennebaker, 2015). Results: Results showed that during the acute phase of COVID-19, people felt more certainty about the present than about the future. In particular, the appraisal dimension of certainty influenced the elicitation of positive feelings through the effect of positive anticipatory states. People with high levels of certainty about the future experienced positive feelings more frequently. The results also suggest that people find it easier to focus on the present moment and experience positive feelings rather than try to predict the future and generate positive feelings based on those predictions. Conclusions: The study is significant, as it is the first to investigate whether certainty may be a strategy for regulating the specific stressor represented by the COVID-19 pandemic. The results highlighted the importance of certainty in coping with environmental threats and stressors.